To Problem Pertaining to Provision of Electric Power Load Schedules of Power Sys- tems while Involving Potential of Power Technological Sources of Industrial Enterprises - B. M. Khroustalev; V. N. Romaniouk; Y. N. Kovalev; N. A. Kolomytskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a possibility to use co-generated complexes having heat technological industrial load for operation in accordance with the requirements of irregularity of electric power generation schedule.